The ontogeny of the reproductive system of Gonaxis Gwandaensis (Preston)(Pulmonata, Streptaxidae) with special reference to the phylogeny of the spermatic conduits of the Pulmonata - Visser, M. H. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1970.